Construction of Biholomorphic Convex Mappings of Order α on Bpn - Ming-Sheng Liu; Fengying Yang; Kit Ian Kou; Changqin Huang (Abstract and Applied Analysis)
Some sufficient conditions for biholomorphic convex mappings of order α on the Reinhardt domain Bpn in Cn are given; from that, criteria for biholomorphic convex mappings of order α with particular form become direct. As applications of these sufficient conditions, some concrete biholomorphic convex mappings of order α   on Bpn are provided.